Distorsiones cognitivas y su incidencia en el estado emocional de un adulto mayor residente en el cantón Vinces - Ramírez Morán, Olga Alexandra (2023)
The present case study was born with the question: How do cognitive distortions influence the emotional state of an older adult residing in the Vinces canton? Given the observations made in an older adult during the praxis of Linkage with society that was carried out previously. Cognitive distortions can be defined as biases when interpreting the information, we receive from the environment and others, these distortions appear as automatic thoughts directed towards the environment, others and ourselves that can generate responses of both an emotional and behavioral. On the other hand, people are emotional beings by nature, which is why we have different emotional reactions based on all the situations we experience, which vary in intensity and duration, determining the type of emotional state. The main objective of this work is to determine the influence that cognitive distortions present in the elderly have on their emotional state, through various techniques and instruments of psychological evaluation, where it was identified that the emotions present in the adult greater are anger and sadness, where the latter lasts longer, determining a condition in the mood.